Circular RNA CircPPP1CB Suppresses Tumorigenesis by Interacting With the MiR-1307-3p/SMG1 Axis in Human Bladder Cancer - Wang, Feifan; Zhang, Yan; Zhou, Xuejian; Chen, Xianwu; Xiang, Jiayong; Fan, Mengjing; Yu, Yanlan; Cai, Yueshu; Wu, Hongshen; Huang, Shihan; He, Ning; Hu, Zhenghui; et al. (Frontiers in Cell and Developmental Biology, 2021)
Circular RNAs (circRNA) is a newly discovered endogenous non-coding RNA (ncRNA), which is characterized with a closed circular structure. A growing body of evidence has verified the vital roles of circRNAs in human cancer. In this research, we selected circPPP1CB as a study object by circRNA sequencing and qRT-PCR validation in human bladder cancer. CircPPP1CB is downregulated in bladder cancer. Functionally, circPPP1CB modulated cell growth, metastasis and EMT process in vitro and in vivo. Mechanically, we performed various experiments to verify the circPPP1CB/miR-1307-3p/SMG1 regulatory axis. Taken together, our results demonstrated that circPPP1CB participates tumor growth, metastasis and EMT process by interacting with the miR-1307-3p/SMG1 axis, and circPPP1CB might be a novel therapeutic target and diagnostic biomarker in human bladder cancer.